Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.tics.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Hippocampal Memory Systems

Abstract: No medications prevent or reverse age-related cognitive decline. Physical activity (PA) enhances memory in rodents, but findings are mixed in human studies. As a result, exercise guidelines specific for brain health are absent. Here, we reexamine results from human studies, and suggest the use of more sensitive tasks to evaluate PA effects on age-related changes in the hippocampus, such as relational memory and mnemonic discrimination. We discuss recent advances from rodent and human studies into the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 166 publications
6
150
1
4
Order By: Relevance
“…Our finding of a relationship between CRF and episodic learning rate aligns with previous findings of positive relationships between CRF and cognitive outcomes (Erickson et al, 2009;Hayes et al, 2013Hayes et al, , 2016Hayes et al, , 2017Szabo et al, 2011), and is supported by a large body of work in animals and humans that has shown beneficial effects of PA on the brain, specifically the hippocampus, and hippocampaldependent learning and pattern separation (Creer, Romberg, Saksida, van Praag, & Bussey, 2010;Hayes et al, 2015;Suwabe et al, 2017;van Praag, Shubert, Zhao, & Gage, 2005). Previous studies have also demonstrated a relationship between CRF and hippocampal volume (for review see Voss et al, 2019). Thus, it is surprising CRF was not related to hippocampal volume in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of a relationship between CRF and episodic learning rate aligns with previous findings of positive relationships between CRF and cognitive outcomes (Erickson et al, 2009;Hayes et al, 2013Hayes et al, , 2016Hayes et al, , 2017Szabo et al, 2011), and is supported by a large body of work in animals and humans that has shown beneficial effects of PA on the brain, specifically the hippocampus, and hippocampaldependent learning and pattern separation (Creer, Romberg, Saksida, van Praag, & Bussey, 2010;Hayes et al, 2015;Suwabe et al, 2017;van Praag, Shubert, Zhao, & Gage, 2005). Previous studies have also demonstrated a relationship between CRF and hippocampal volume (for review see Voss et al, 2019). Thus, it is surprising CRF was not related to hippocampal volume in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…First, it extends previous exercise intervention studies (e.g., Erickson et al, ; Jonasson et al, ; Kleemeyer et al, , among others) not only to cognitively healthy young adults, but also to the hippocampal subfield level, and second, in this study, we uniquely combined an assessment of behavioral pattern separation with volumetric measurement of hippocampal subfields, extending previous work on exercise effects on behavioral pattern separation in young adults (DĂ©ry et al, ) and, critically, providing the most direct comparison with prominent animal models of exercise‐induced hippocampal plasticity mechanisms to date. A 2019 review by Voss et al has highlighted a clear need for research on the effects of aerobic exercise and other exercise modalities on behavioral pattern separation in humans (Voss et al, ). The results presented here make an important step toward filling this critical knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest evidence for a relationship between CRF, hippocampal volume, and memory would come from a randomized controlled trial involving a structured exercise intervention known to increase CRF. Many such studies have shown evidence of a relationship between aerobic exercise and cognition (for review see A. F. Kramer & Colcombe, 2018;Voss et al, 2019), though none have utilized a task like the EAL task, which specifically targets aspects of hippocampal function that are critically important for accumulating episodic information over repeated occurrences. Nonetheless, our findings do align with previous evidence of exercise interventions resulting in increased brain structure, brain function, and cognition, as well as with other cross-sectional studies of CRF, hippocampal volume, and various aspects of memory (Erickson et al, 2009;Hayes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%